Comparison of anthropometrics and physical performance in professional baseball pitchers - Donahue, P. T.; Beiser, E.; Wilson, S. J.; Garner, J. C. (Journal of Trainology, 2020)
Objectives: Previous investigations have shown that differences exist between positional groups within a team, which has led to more specific methods of training to enhance performance for that positional group during competition. The purpose of this investigation was to examine anthropometric and physical performance measures between these two classifications of baseball pitchers. Design and Methods: Twenty professional pitchers completed a battery of test including anthropometrics, body composition, vertical jump, sprint cycling, and shuttle run. All testing was performed during the preseason prior to the start of competition. Independent sample t-tests were performed on each variable between starters and relievers. Results: Significant differences were seen between starters and relievers in height (p < 0.05). No other variables showed statistically significant differences, though moderate effect sizes were present for sprint cycling and shuttle run times. Conclusion: Findings of this investigation lend support to training pitchers in a similar manner as no differences were seen been groups based on physical performance and anthropometric.